Polycystic ovaries and infertility: Our experience - Lavanya Rajashekar; Deepika Krishna; Madhuri Patil (Wolters Kluwer Medknow Publications, 2008)
Background: Polycystic ovary syndrome (PCOS) is one of the most common (15-20%) endocrine disorders in women of childbearing age. Although it is a major cause of infertility, its etiology remains unknown and its treatment difficult. Aim: To evaluate the incidence, treatment and outcome of patients with PCOS. DESIGN: Retrospective analysis. Materials and Methods: PCOS patients (914 of the 1057) attending the outpatient department (OPD) from June 2003 to February 2008 were evaluated for this study. Of the 914 patients investigated, 814 came for treatment and these patients were studied for hormonal disturbances and their response to various modalities of treatment. Results: Of the 2270 infertility patients, 46.50% (1057) had PCOS, out of these, 86.47% (914) were investigated and 77% (814) came for treatment. Our overall pregnancy rate was 48.40% (394/814). The pregnancy rate per cycle with timed intercourse (TI) was 44.77% (47/105), 17.09% (286/1673) with intrauterine insemination (IUI), 29.82% (51/171) with in vitro fertilization (IVF) and 22.22% (10/45) with frozen embryo transfer (FET). The maximum number of pregnancies (85.29%, 284/333) were achieved in the first three treatment cycles. The abortion rate was 19.01% (73/384) and the incidence of ectopic pregnancy was 5.47% (21/384). Complications seen were in the form of ovarian hyperstimulation (OHSS), retention cyst on day two and multiple pregnancies in 11.71% (228/1946) of the total treatment cycles. Conclusion: Most PCOS symptoms could be adequately controlled or eliminated with proper diagnosis and treatment. Thus, ovulation induction (OI) protocols and treatment modalities must be balanced for optimal results.